Determining the potential of sonic bloom in inducing rice resistance (Oryza sativa) against the attack of bacterial leaf blight disease caused by Xanthomonas oryzae - Algina, Azka; Yulianti, Syifaa Yunita; Syamsyiah, Rohimatus; Yasminingrum, Veadora; Nur Vendi, Bergas Frenli; Dewi, Vira Kusuma (Kultivasi, 2023)
Xanthomonas oryzae which causes bacterial leaf blight disease is one of the main pathogens that attack rice crops. The threat of losing rice yields due to X. oryzae needs to be avoided by implementing appropriate control strategies. Sonic bloom has the potential to induce plant immunity against diseases. Hence, this study aimed to examine the potential of sonic bloom in inducing rice resistance to bacterial leaf blight. The experiment was arranged in a Randomized Block Design (RBD) with five treatments and three replications. The treatments consisted of several frequencies, namely PR (0.5 - 1 kHz and inoculated with X. oryzae), PS (3 - 5 kHz and inoculated with X. oryzae), PT (7 - 10 kHz and inoculated with X. oryzae), KP (inoculated with X. oryzae without sonic bloom treatment), KN (no bacterial inoculation and sonic bloom treatment). The results showed that all sonic bloom treatments (LF, MF, HF) had a significant effect on increasing the intensity of BLB disease in rice plants. This showed that sonic bloom in this range does not have the potential to induce rice plant resistance to BLB. Further research to find out the causes of this is needed.